Prevalence of preoperative delirium and associated factors in elderly hip fracture patients at King Chulalongkorn Memorial Hospital - Sitthisarunkul, Warong; Thipakorn, Yanin; Thisayakorn, Paul (Chulalongkorn Medical Journal, 2023)
Background: Preoperative delirium in hip fracture is under-studied. Effective diagnosis, prevention, and management of preoperative delirium may be able to reduce the incidence of the postoperative complications. Objective: To study the prevalence of preoperative delirium and its associated factors in elderly patients who underwent hip fracture surgery. Methods: This is a cross-sectional study which collected the data from patients aged more than 65 years who underwent hip surgery at King Chulalongkorn Memorial Hospital. Preoperative cognitive status assessment was done by using the Thai Mental State Examination (TMSE) and The Confusion Assessment Method-Thai (CAM-T) on the day before surgery. The DSM-V criteria for delirium was used to confirm the diagnosis. Postoperative factors were assessed at bedside on day 2 after surgery and on discharge. Results: There were 104 patients recruited in the study with a mean age of 81.3 years. In total, 24 patients developed preoperative delirium which equaled to 23.0%. Factors associated with preoperative delirium were cognitive impairment, Alzheimer’s dementia, dyslipidemia, respiratory tract disease, history of previous delirium, a length of hospital stay before surgery of more than 48 hours and a TMSE score lower than 23. Preoperative delirium was associated with postoperative pulmonary complications and longer hospital stay. Conclusion: The prevalence of preoperative delirium in hip fracture elderly patients was 23.0%. Many preoperative clinical factors and postoperative adverse outcomes were associated with preoperative delirium. Therefore, routine screening for delirium in elderly with hip fracture before the surgery may provide a benefit on the clinical outcome.